From Ramayana to Sinta Obong: A Comparative Literary Study for Literacy Learning in Higher Education - Mustopa, Rizki Akbar; Rivanti, Ari Nursenja; Ambarsari, Nais (Program Studi Tadris Bahasa Indonesia Institut Agama Islam Negeri Lhokseumawe, 2025)
This study aims to analyze the transformation of plot, characters, characterization, setting, and themes in Ramayana by Nyoman S. Pendit and Sinta Obong by Adrian Kresna, as well as their implications for literacy education in higher education. Using a qualitative approach and a comparative literature analysis method, the study finds that although both novels share a similar ending, they differ significantly in narrative structure, conflict development, and character representation. Sinta Obong presents a modern reinterpretation by emphasizing psychological depth, introducing more complex layers of setting, and expanding emotional conflicts that do not appear in Ramayana. These transformations illustrate a process of meaning negotiation that reflects shifts in cultural and ideological values. The findings indicate that comparative literary analysis can strengthen students’ critical literacy, cultural literacy, and intertextual literacy, making it highly relevant for literacy instruction in higher education.